2015
DOI: 10.1002/sdtp.10123
|View full text |Cite
|
Sign up to set email alerts
|

P‐56: High Resolution Organic Light‐Emitting Diode Panel Fabricated by Ink Jet Printing Process

Abstract: Displays using organic light emitting diodes (OLEDs) Author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…As a result, electroluminescent pixels with position and size accuracy within one micrometre, required for this technology, can be processed. High resolutions exceeding 200 pixels per inch, that are suitable for large size but also for medium and small size displays can be created using this approach [ 108 ].…”
Section: Inkjet Printing Of Light Emitting Devicesmentioning
confidence: 99%
“…As a result, electroluminescent pixels with position and size accuracy within one micrometre, required for this technology, can be processed. High resolutions exceeding 200 pixels per inch, that are suitable for large size but also for medium and small size displays can be created using this approach [ 108 ].…”
Section: Inkjet Printing Of Light Emitting Devicesmentioning
confidence: 99%
“…For the panel development, the panel size of a 14-inch and the 65-inch panel were produced by the IJP process [3][4]. For the middle size application, it has been demonstrated that it is possible to produce high resolution displays by IJP [5]. Furthermore, uniformity study of the pixel arrangement designs on high resolution IJP OLED were discussed on P. Y. Chen et al to address which pixel arrrangement design is suitable for better uniformaity and OLED performance.…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…C. L. Chen et al [1] and P. Y. Chen et al [2] demonstrated good OLED performances in a 14-inch and 65-inch panel produced by the IJP process using oxide thin film transistors (oxide-TFTs) as the backplane. For the media size application, P. Y. Chen et al [3] demonstrated that it is possible to produce high resolution displays despite the limitations in the IJP technique. In this paper, we successfully demonstrated a 167 ppi OLED panel fabricated by the IJP process.…”
Section: Objective and Backgroundmentioning
confidence: 99%